Achievement of higher biomass, yield and quality of essential oil of Tagetes minuta L. through optimizing the sowing method and seeding rate - Pal, Probir Kumar; Mahajan, Mitali; Thakur, Babit Kumar; Kapoor, Priya; Shivani, (Frontiers in Plant Science, 2023)
Tagetes minuta L. is known as an industrial crop in the world due to possessing essential oil that is extensively used in the perfumery and flavour industries. The crop performance is influenced by the planting/sowing methods (SM) and seeding rate (SR); however, the effects of these variables on biomass yield and quality of essential oil of T. minuta remain unclear. As a comparatively new crop, responses of T. minuta to different SM and SR have not been studied in the mild temperate eco-region. Thus, biomass and essential oil yield response of T. minuta (variety Himgold) to SM (line-sowing and broadcasting) and SR (at 2, 3, 4, 5, and 6 kg ha-1) were investigated. The overall fresh biomass of T. minuta ranged from 16.86 to 28.13 Mg ha−1, while essential oil concentration in fresh biomass varied from 0.23 to 0.33%. Irrespective of SR, the broadcasting method produced significantly (p ≤ 0.05) higher fresh biomass yield by about 15.8 and 7.6% compared with line-sowing during 2016 and 2017, respectively. An increase in biomass yield was noted as the SR increased up to 4 kg ha−1. The SR at 4 kg ha−1 registered about 41.9- 56.1% and 3.3−10.3% higher biomass yield than the SR at 2 kg ha−1 and 6 kg ha−1, respectively. No significant (p ≥ 0.05) differences in essential oil concentration in fresh biomass were observed due to the different SM and SR. Thus, T. minuta may be sown by the broadcasting method in the mild temperate eco-region with an SR of 4 kg ha−1.